DOES UNCERTAINTY AFFECT FIRM PERFORMANCE? EVIDENCE FROM INDONESIA - Heniwati, Elok; Novita, Novita; Yunita, Khristina (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2023)
This study evaluates the relationship between firm performance and stock price while incorporating the uncertainty due to the COVID-19 pandemic as a control variable. A research model was developed separating two periods: before (2019) and during (2020) the COVID-19 pandemic. The sample consisted of all companies of LQ45 Index members. This study examined quarterly panel data and a total of 360 observations. Next, the analysis evaluates the impact of actual performance on share prices using Structural Equation Modeling, more precisely SmartPLS, as an analysis tool. The results show that the profitability, solvency, and activity ratios influence the stock price of LQ45 companies both before and during the COVID-19 pandemic, except the liquidity ratios. Meanwhile, the uncertainty has no influence on the stock price of LQ45 companies both before and during the COVID-19 pandemic. These findings imply that policymakers should respond to drivers of stock performance and regulate strategic decisions accordingly in order to mitigate their long-term impact.JEL: M40, M41.